The Seeing Stone - Kevin Crossley-Holland (United States Scholastic US, 2002)
It is 1199 and young Arthur de Caldicot is waiting impatiently to grow up and become a knight. One day his father's friend Merlin gives him a shining piece of obsidian and his life becomes entwined with that of his namesake, the Arthur whose story he sees unfold in the stone. In this many-layered novel, King Arthur is seen as a mysterious presence influencing not just one time and place but many. The 100 short chapters are almost like snapshots not only of the mythic tales of King Arthur, but the earthy, uncomfortable reality of the Middle Ages.
Keywords: Historical Fiction -- Historical Fiction